1962
DOI: 10.2135/cropsci1962.0011183x000200050010x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Seven Methods of Measuring Earliness of Crop Maturity in Cotton1

Abstract: REVIEW OF LITERATURE Extensive studies on the growth pattern of the cotton plant and the characteristics of the different varieties that condition early maturity have been reported by Ewing (3), Martin et al. (8), Harland (5), McNamara et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
2

Year Published

1969
1969
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Earliness, a distinctive characteristic of short-season cotton, is a complex agronomic trait of a quantitative genetic nature [3]. In terms of plant development, earliness may be described in reference to budding date, flowering timing (FT) and the whole growth period (WGP) [4]. Other agronomic traits, such as plant height (PH), node of the first fruiting branch (NFFB) and height of the NFFB (HNFFB), have also been used as earliness indexes [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Earliness, a distinctive characteristic of short-season cotton, is a complex agronomic trait of a quantitative genetic nature [3]. In terms of plant development, earliness may be described in reference to budding date, flowering timing (FT) and the whole growth period (WGP) [4]. Other agronomic traits, such as plant height (PH), node of the first fruiting branch (NFFB) and height of the NFFB (HNFFB), have also been used as earliness indexes [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Rauf et al (2005) reported that importance of additive gene action for number and heigth of node first fruiting branch. The earlier studies of earliness in cotton number of node first sympodial branch, date of first square and date of first flower (Richmond and Radwan 1962), harvested rate of first picking (Richmond and Ray 1966), number of node first sympodial branch and date of first flower (Munro 1971), number of node first sympodial branch and harvested rate of first picking (Tiffany and Nalm 1981), number of node first sympodial branch, date of first square, date of first flower and harvested rate of first picking (Godoy 1994; Godoy and Palomo 1999), number of node first sympodial branch (Iqbal et al 2003) were found reliable for estimation of earliness of cotton plant. They reported that these earliness characters may use efficiently in selections of early genotypes.…”
mentioning
confidence: 99%
“…In China, the cotton‐planting regions have been divided into several agro‐ecological zones based on temperature, photoperiod, frost date and other climatic factors, all of which require early‐maturing cotton varieties (Yu and Xia 2003). Previous research has shown that early maturity in cotton was related to morphological and developmental variables (Richmond and Radwan 1962, Godoy and Palomo 1999). However, the efficiency with which these factors can be manipulated depends considerably on understanding the inheritance and interrelationships among the determinants of early maturity.…”
mentioning
confidence: 97%